Dietary Changes in Fasting Levels of Factor VII Coagulant Activity (FVII: C) Are Accompanied by Changes in Factor VII Protein and other Vitamin K-dependent Proteins - Bladbjerg, E M; Tholstrup, T; Marckmann, P; Sandström, B; Jespersen, J (Thrombosis and Haemostasis, 1995)
The mechanisms behind dietary effects on fasting coagulant activity of factor VII (FVII: C) are not clarified. In the present study of 15 young volunteers, two experimental diets differing in composition of saturated fatty acids (C18:0 [diet S] or C12:0 + C14:0 [diet ML]) were served for 3 weeks each. Fasting blood samples were collected before and after the dietary regimen and analysed for triglycerides, FVII:C, and protein concentrations of FVII, FII, FX, protein C, CRP, albumin, fibrinogen, and F1+2. FVII:C was significantly reduced on diet S compared with diet ML. This was accompanied by a decrease in FVII protein, F1+2 and the vitamin K-dependent proteins FII, FX, and protein C. In contrast, no changes were observed in triglycerides, FVII:C/FVII: Ag, albumin and CRP. Fibrinogen was increased on diet S compared with diet ML. Our findings suggest that the change in fasting FVII:C was part of a general change in concentrations of vitamin K-dependent proteins.